Addictions and school performance in Torreón, México: a case study. - Mayorga-Barajas, Ana Cecilia; Mendez-Ramirez, Oswaldo; De La Torre Pacheco, Sindy Yaneth (Advances in Social Sciences Research Journal, 2016)
Drug use analysis is relevant not only from the perspective of illegal trafficking, but also from the perspective of microanalysis from users, specifically, the ways in which drugs are presented in school spaces and its consequences. In a first approach to the study population, it was found that the most frequent problems were school underachievement and possible defection. So we proceeded to develop a hypothetical model where the variables considered were school performance and intensity of drug use. This is a quantitative correlational study that analyses 218 (N = 218) questionnaires in a secondary school (junior high) located in Torreon, Coahuila. After running correlational and regression models two main conclusions were reached: (a) the variables related to drug use do not directly or significantly affect school performance and (b) the intensity in consumption drug depends on the reasons for the consumer to do so, which is determined by the place where drugs are offered to the subject and it directly affects the desire to drop out.